Konsepsi Negara Sejahtera Menurutal-Farabi - Diding Sariding; Siti Ngainnur Rohmah (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
The welfare state is an ideal country whose development is focused on improving welfare. This is can doing through giving a more important role to the state in providing universal and comprehensive social services to its citizens. The choice of such a country is also the same as what is thought by a Muslim philosopher named Al-Farabi. Al-Farabi's thought in politics such as the main state resembles the ideal state concept of Plato. The leader is the first mover of society to get happiness, as is the position of the heart in the body, while the other body members are helpers to produce the happiness that they aspire to. This paper presents the thoughts of an Islamic philosopher named Al-Farabi about the Prosperous State of Prosperity. This paper analyzes analytically and explores critically Al-Farabi's view of a State and the conception of a Prosperous State in Islam. The study uses qualitative research methods with a literary approach. The data obtained comes from several books and other sources about the conception of a Prosperous State.